Electron-rich two-dimensional molybdenum trioxides for highly integrated plasmonic biosensing - Zhang, Nancy Meng Ying (2019)
Two-dimensional (2D) plasmonic materials facilitate exceptional light–matter interaction and enable in situ plasmon resonance tunability. However, surface plasmons of these materials mainly locate intrinsically at the long wavelength range that are not accessible for practical applications. To address this fundamental challenge, transition metal oxides with atomically layered structure as well as free carriers doping capability have been considered as an alternative class of 2D plasmonic material for achieving tunable plasmonic properties in the visible and near-infrared range. Here, we synthesize few-layer α-MoO3 nanoflakes that are heavily doped with free electrons via H+ intercalation. The resultant substoichiometric MoO3–x nanoflakes provide strong plasmon resonance located at ∼735 nm. Moreover, the MoO3–x nanoflakes carrying positive charges show stable attachment to polyanions functionalized microfiber and good affinity to negatively charged biomolecules. Our experimental demonstration of fiber-optic biosensing platform provides a detection limit of bovine serum albumin as low as 1 pg/mL, and proves the feasibility and prospects of employing 2D MoO3–x plasmonic nanoflakes in highly integrated devices compliant with frequently used and cost-effective optical system.